HUBUNGAN PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DENGAN KREATIVITAS MENGAJAR PENDIDIK PAUD DI KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR - Pangarti, Wanda Mingga; Chairilsyah, Daviq; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the relationship between information technology and communication with creativity teaching early childood education in Tapung Hilir Sub-District, Kampar Regency. This research is a correlation study consisting of independent variables (x), namely information and communication technology and the dependent variable (y), namely teaching creativity of educators. The population and samples in this study were 83 early childood education in Tapung Hilir District, Kampar Regency. The instrument for collecting data on the relationship of information technology and communication with teaching creativity of educators uses questionnaires (questionnaires). The data collection technique in this study was using a scale. All statements are anchored or the questionnaire is presented in a Likert scale consisting of five answer choices namely: always (SL), often (SR), sometimes (KD), rarely (JR), never (TP). As the item selection criteria based on item correlation, the total Likert scale is most often used, the limit of the rxy value is 0.649. From the calculation it is known that r count> r table, for the significance level of 5% = 0.649> 0.254, while at the significance level 1% = 0.649> 0.330. This means that Ha can be accepted and Ho is rejected. So it can be concluded that the correlation between variable X (utilization of Information and Communication Technology) and variable Y (creativity in teaching PAUD educators) there is a positive relationship between the two variables. In other words if the score X increases, the Y score also increases.Key Words: Information and Communication Technology, Teaching Creativity